INNOVATION AND INVESTMENT POLICY AS A TOOL FOR ACCELERATING HUMAN CAPITAL DEVELOPMENT - BUZETSKYI, Ihor; VITKOVSKYI, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article carries out a comprehensive study of innovation and investment policy as a tool for boosting human capital development in Ukraine, considering the deep transformation processes that intensified after the start of the full-scale war in 2022. In the context of the growing role of knowledge, digital technologies, and intellectual capital, effective coordination of innovation and investment policy is a determining factor in ensuring sustainable development. A comparative characteristic of these policies made it possible to identify their functional features, mechanisms of influence on human capital, and their role in the modernization of the knowledge economy. Innovation policy is characterized as a source of demand for new knowledge, competencies, technologies, and investment policy as a material and financial basis for implementation. The strategic prerequisites until 2022 were analyzed, particularly regulatory documents and program guidelines forming state innovation and investment policy foundations, including the National Economic Strategy 2030, digitalization strategies, entrepreneurship support, and scientific and technological development. It was determined that despite the political desire for reforms, institutional capacity and financing remained limited, and the investment indicators in R&D were significantly lower than in Europe. The study focuses on the transformation of state policy in innovation and investment after the start of the full-scale invasion. It reveals changes in strategic priorities, reorientation to support economic sustainability, preservation of entrepreneurial potential, digital transformation, and international cooperation. The role of interdepartmental coordination, public-private partnerships, and flexible instruments for stimulating human capital is increasing in the new conditions. Special attention is paid to analyzing the problems of human capital development in wartime. Three key blocks of threats are identified: first, large-scale losses of labor resources due to mobilization, emigration and forced displacement; second, physical destruction of educational, scientific and innovative infrastructure; third, increased socio-economic instability, which led to a reduction in investments in human development by the state, business and households. It is emphasized that boosting human capital development requires financial resources, strategic management, an adaptive education system, flexible professional training, and preservation of the nation’s intellectual core. Summarizing the results, the authors justify the need to implement a coordinated, multi-level innovation and investment policy as a key condition for the restoration and qualitative renewal of human potential in the post-war period.